A secured e-tendering modeling using misuse case approach - Mohd, Haslina; Robie, Muhammad Afdhal Muhammad; Baharom, Fauziah; Muhd Darus, Norida; Saip, Mohamed Ali; Yasin, Azman (2016)
Major risk factors relating to electronic transactions may lead to destructive impacts on trust and transparency in the process of tendering.Currently, electronic tendering (e-tendering) systems still remain uncertain in issues relating to legal and security compliance and most importantly it has an unclear security framework.Particularly, the available systems are lacking in addressing integrity, confidentiality, authentication, and non-repudiation in e-tendering requirements.Thus, one of the challenges in developing an e-tendering system is to ensure the system requirements include the function for secured and trusted environment.Therefore, this paper aims to model a secured e-tendering system using misuse case approach.The modeling process begins with identifying the e-tendering process, which is based on the Australian Standard Code of Tendering (AS 4120-1994).It is followed by identifying security threats and their countermeasure.Then, the e-tendering was modelled using misuse case approach.The model can contribute to e-tendering developers and also to other researchers or experts in the e-tendering domain.